An Investigation into the Fast-Food Consumption Habits of Public Health and Nursing Students at the University of Sunderland in London, UK - Parvin, Sauda; Kabir, Russell; Parsa, Ali Davod; Sivasubramanian, Madhini (Libyan International Medical University Journal, 2023)
Background It is generally believed that university students may consume nutritionally deprived foods, which can lead to weight gain and long-term health complications.Aims This research aims to illustrate the fast-food consumption pattern of nursing and public health students at the University of Sunderland in London, United Kingdom.Methods This cross-sectional study involved 235 nursing and public health students. The survey included a validated questionnaire, which provided insights into the general characteristics of the participants, their fast-food consumption patterns, reasons for fast-food consumption, and knowledge about fast food. The data was analyzed using SPSS version 21, chi-squared tests conducted to determine the significance of the relationships between different variables. Odds ratio (OR) was utilized to assess the association between two variables.Results About 50.6% of the students were aged between 20 and 29 years, and 77.4% patients were female, 46.8% single, and 31.1% unemployed. About 26.4% of the students were overweight, and 14.5% were obese. Fast-food consumption occurred during lunchtime (48.1%), followed by evening (37.0%). OR for fast-food enjoyment decreased significantly with age (from 0.54 for the age group 30–39 years old to only 0.13 in the age group 50–59). Married individuals were less likely to enjoy fast food than single nurses (OR = 0.54). Body mass index (BMI) was positively and significantly associated with fast-food enjoyment, with the OR increasing significantly with increasing BMI (from 5.9 for the BMI 18–24 kg/m2 up to 11.6 for BMI above 30 kg/m2). Females were more likely to enjoy the taste of fast food than males (48.4 vs. 32.1%). Males were more likely to favor fast food than females due to lack of cooking skills (7.5 vs. 1.6%), to save time (47.2 vs. 30.2%), and to fulfill their basic needs (26.4 vs. 11%). About 96.2% of females and 92.5% of males acknowledged that excessive consumption of fast food could lead to health problems.Conclusion Fast-food consumption exhibited variability among university students, with females being more inclined toward the taste and males toward convenience. Age exhibited a negative association, while BMI displayed a positive association with fast-food enjoyment. Both genders acknowledged that excessive consumption of fast food could lead to health issues.
Keywords: fast food; consumption; BMI; university students; factors; London